Permainan inovatif Leghezo sebagai media edukasi kesehatan untuk anak-anak - Widodo Hariyono; Elisda Septiyani (Universitas Ahmad Dahlan, 2019)
Golden ages phase is an important period of growth and development of the children. This period is a very good time to cultivate the values of the character of goodness which will hopefully be able to shape his personality. One of them is about living clean and healthy. Leghezo is health education games for children. Leghezo was present because of the limited health education media at the time of the widespread use of gadgets by children. Leghezo is a product development of the Research and Development study level 3. The stages of the research include data collection, planning, product development, validation, and product trials. The feasibility of the product is based on the results of the assessment of media experts, material experts, and Elementary School (SD) students as test subjects. Data collection techniques using observation and questionnaires. Data analysis with qualitative descriptive. The results of the study, the assessment of media experts score 4.36 (feasible category), expert assessment of the material score 4.90 (feasible category), the initial field trial results are 100% (feasible category). In conclusion, the innovative Leghezo game is worthy of being a health education media for children aged between 7-13 years.